2022
DOI: 10.1128/spectrum.00326-22
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Patients with Delftia acidovorans Infections: a Retrospective Cohort Study

Abstract: Delftia acidovorans ( D. acidovorans ) is a Gram-negative bacteria that can cause infection in immunocompetent and immunocompromised individuals. The current knowledge comes mainly from case reports and case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Conversely, higher resistance rates were observed for gentamicin (92.3%). 37 Our observations pertaining to antibiotic susceptibility closely paralleled those outlined in Højgaard et al's work, with over 85% of isolates exhibiting susceptibility to meropenem, imipenem, ceftazidime, and piperacillin-tazobactam and a 75% susceptibility rate for cefepime. Our study showed that the isolates had a high rate of resistance to aminoglycosides (96%).…”
Section: Antimicrobial Susceptibility Pattern Of Delftia Acidovoranssupporting
confidence: 87%
See 1 more Smart Citation
“…Conversely, higher resistance rates were observed for gentamicin (92.3%). 37 Our observations pertaining to antibiotic susceptibility closely paralleled those outlined in Højgaard et al's work, with over 85% of isolates exhibiting susceptibility to meropenem, imipenem, ceftazidime, and piperacillin-tazobactam and a 75% susceptibility rate for cefepime. Our study showed that the isolates had a high rate of resistance to aminoglycosides (96%).…”
Section: Antimicrobial Susceptibility Pattern Of Delftia Acidovoranssupporting
confidence: 87%
“…5 The most recent and comprehensive cohort study, conducted by Højgaard et al, has significantly contributed to our understanding of D. acidovorans infections. 37 This study encompassed 59 patients between 2002 and 2020 at a tertiary referral center in Denmark, representing the largest cohort to date. Within these patients, a sex distribution of 35 male patients (59%) and a median age of 47 years at the time of infection were observed.…”
Section: Characteristics Of the Patients With Delftia Acidovorans Inf...mentioning
confidence: 99%
“…Rhizobium strains were among the most consistently isolated bacteria from subsurface Mediterranean sapropels ( Suess et al, 2004 , 2006 ). In contrast, the hydrocarbon-degrading freshwater and soil bacterium and opportunistic pathogen Delftia ( Wen et al, 1999 ; Højgaard et al, 2022 ), the heavy metal-resistant soil bacterium Cupriavidus ( Vandamme and Coenye, 2004 ) and the plant-and human-associated bacterium Stenotrophomonas ( Ryan et al, 2009 ) lack marine or subsurface associations. We caution that these sequences were most likely introduced as contaminants during handling of samples, reagents or PCRs, and we are reporting them to provide reference sequences for critical evaluations of microbial community surveys in extreme habitats ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clones from the deeper core section (260–280 cmbsf) were affiliated with the gammaproteobacterial genus Acinetobacter , capable of hydrocarbon degradation in hydrocarbon-polluted soils or in oilfield production liquids ( Chaîneau et al, 1995 ; Gong et al, 2012 ). Sequences of the gamma- and betaproteobacterial genera Stenotrophomonas (associated with human clinical samples; Ryan et al, 2009 ), Delftia (an opportunistic emergent pathogen; Højgaard et al, 2022 ) and Achromobacter (described from human sample material; Yabuuchi and Yano, 1981 ), were found in the deep gravity core sample (260–280 cmbsf) and represent likely contaminants from human contact and handling in the lab.…”
Section: Resultsmentioning
confidence: 99%
“…Colonization or persistent infection with Delftia acidovorans was observed in a relatively small proportion, approximately 7 % of patients, although most of these patients had at least one underlying comorbidity. Notably, the all-cause mortality within the first year after infection was found to be high [ [31] , [32] , [33] ]. We also identified a significant expansion of Streptomyces violaceusniger , Phenylobacterium sp.…”
Section: Discussionmentioning
confidence: 99%